2021
DOI: 10.1161/hypertensionaha.120.14909
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Supplementation Attenuates Pulmonary Hypertension via Regulation of Magnesium Transporters

Abstract: Pulmonary hypertension (PH) is characterized by profound vascular remodeling and altered Ca 2+ homeostasis in pulmonary arterial smooth muscle cells (PASMCs). Magnesium ion (Mg 2+ ), a natural Ca 2+ antagonist and a cofactor for numerous enzymes, is crucial for regulating diverse cellular functions, but its roles in PH remains unclear. Here, we examined the roles of Mg 2+ and its transporters in PH development. Chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 60 publications
1
31
1
Order By: Relevance
“…Nonetheless, the function of TRPM7 in skeletal muscle physiology and muscle cell differentiation has not been elucidated yet. SLC41A1 is expressed in smooth muscle cells and has a role in regulating their proliferation and migration [14], while presently no data are available for MagT1. As for TRPM7, it is still obscure whether SLC41A1 and MagT1 play a role in myogenic differentiation and in mature skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the function of TRPM7 in skeletal muscle physiology and muscle cell differentiation has not been elucidated yet. SLC41A1 is expressed in smooth muscle cells and has a role in regulating their proliferation and migration [14], while presently no data are available for MagT1. As for TRPM7, it is still obscure whether SLC41A1 and MagT1 play a role in myogenic differentiation and in mature skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…RVSP was more than doubled (CON: 24.76 ± 2.38 mmHg, n = 19; MCT: 58.95 ± 8.84 mmHg, n = 23, P < 0.001; Figure 1a–c) and the right heart mass ratio, RV/(LV+S), increased notably (CON: 26.82± 3.37%, n = 15; MCT: 56.25 ± 10.52%, n = 16, P < 0.001; Figure 1d). The morphometric analysis of the pulmonary artery has been detailed in previous research (Liu et al., 2012; Wang et al., 2021). All this suggests that MCT induced profound PAH.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have documented that in the vascular rings of chronic hypoxia‐treated mice, high [Mg 2+ ] e can mitigate the endothelin‐1 (ET‐1)‐activated vasoconstriction and adjust vasorelaxation via the release of NO in the endothelial cells (Mu et al., 2018). Moreover, Mg 2+ supplementation can mitigate the progression of PAH by regulating the Mg 2+ transporters in monocrotaline (MCT)‐treated PAH rats (Wang et al., 2021), and decrease the mean pulmonary arterial pressure in experimental PAH rats (Kh et al., 2000). Besides, studies have shown that pulmonary vascular remodelling mainly occurs in the small and medium pulmonary arteries with a diameter of <500 ÎŒm and is most significant in those with a diameter of 200–300 ÎŒm (Hislop & Reid, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In human and Sprague-Dawley rat PASMCs with PAH, TRPM7 is downregulated, which activates the mitogen-activated extracellular signal-regulated kinase (MEK)/extracellular-signal-regulated kinase (ERK) pathway and decreases cellular Mg 2+ levels, thus promoting SMC proliferation exacerbating PAH [59]. TRPML1 is crucial for the initiation of Ca 2+ sparks in SMCs and the regulation of vascular contractility and blood pressure, and TRPML1-knockout mice are spontaneously hypertensive [60].…”
Section: Mechanosensitive Mechanisms and Their Role In Vsmcsmentioning
confidence: 99%
“…In an SHR disease model, multiple isoforms of TRP channels are activated and activated TRP mediates elevated intracellular Ca 2+ and Na + [50]. In PAH, TRPM7 is downregulated to activate the MEK/ERK pathway and intracellular Mg 2+ levels are reduced [59]; in addition, mechanical stretch potentiating the Ang II type 1/EGFR/ERK-dependent signaling pathway directly regulates VSMC proliferation induced in SHR [133]. Activation of tyrosine kinase phosphorylation in SMCs in hypertension [125] and activation of the MAPK signaling pathway both promote VSMC proliferation and migration [203].…”
Section: Mechanosensitive Pathways In Smcs Are Involved In Vascular R...mentioning
confidence: 99%